Deciding on thresholds for clinical relevance of PROMIS-upper extremity v2.0 in patients with upper extremity injury - Suus G. J. van Bruggen; Lore E. de Vreeze; Charlotte M. Lameijer; Frank W. Bloemers; Caroline B. Terwee (Quality of Life Research, 2026)
Abstract Purpose In this study we focused on gaining better interpretation of the PROMIS-Upper-Extremity v2.0 (PROMIS-UE v2.0) T-score scale for measuring upper extremity function in patients with upper extremity injuries (UEIs). This is fundamental in order to clearly understand the clinical relevance of these outcomes. The aim of this study was to identify interpretive thresholds for mild, moderate and severe upper extremity function problems for PROMIS-UE v2.0 T-scores, in patients with UEIs, by performing a vignettes study. Methods A qualitative vignette study, based on the PROMIS-UE v2.0 and its item response theory model. Designed vignettes were tested in pilot expert- and patient focus groups. The vignettes were ranked by participants by functioning level and interpretive threshold values were proposed. Results This resulted in consensus on the following interpretive thresholds: no problems—mild problems at T-score 45, mild problems—moderate problems at T-score 32.5 and moderate problems—severe problems at T-score 25. The thresholds provide additional information on interpretation of a larger range of the T-score scale, not only the evidently low or high T-scores. Conclusion This study provides clinically meaningful interpretive thresholds for interpreting PROMIS-UE v2.0 T-scores in patients with UEI, supporting more patient-centred interpretation of treatment outcomes. We recommend using these interpretive thresholds in clinical practice to support the interpretation of patient-reported treatment outcomes and facilitate shared decision-making. Future research with regards to influencing factors on ranking of the vignettes should follow.